Handbook of research on strategic alliances and value co-creation in the service industry - Rozenes, Shai; Cohen, Yuval (IGI Global, Disseminator of Knowledge, 2017)
"[This book] is a comprehensive source of scholarly material on frameworks for the effective management of value co-creation in contemporary business contexts. Highlighting relevant perspectives across a range of topics, such as public relations, service-dominant logic, and consumer culture theory, this publication is ideally designed for professionals, researchers, graduate students, academics, and practitioners interested in emerging developments in the service industry" - Provided by publisher
Keywords: Strategic alliances (Business); Customer relations; Economic value added